Karakteristik Proksimat dan Organoleptik Ubi Jalar Merah (Ipomea batatas (L.) Lam.) Pada Berbagai Proses Pemasakan - Dwi Febriantini; Ade Heri Mulyati; Diana Widiastuti (Institut Pertanian Bogor, 2016)
Sweet potato (Ipomea batatas (L.) Lam.) is one of functional foods that can maintain and improve human health. Due to the very hard texture of red sweet potato, it cannot be consumed directly. Therefore, it requires various cooking methods in order to be more suitable for consumption. This study aimed at determining effects of various cooking methods on the proximate and sensory properties of red sweet potato. The research covers various cooking methods of red sweet potato through boiling, frying, baking, steaming, and one treatment without cooking process (fresh) which was used as a control. The results show that various cooking methods affect almost all testing parameters significantly, except for ash content. Baked red sweet potato has the lowest moisture content (38,75%) and the highest sugar value as sucrose (17,17%). Sensory properties test results show that the most preferred red sweet potato is fried red sweet potato.